Knowledge of WKRI Padang City Members on Hypertension - Bun Yurizali; Nurmaines Adhyka (Jurnal Keperawatan Silampari, 2023)
This study aims to provide an overview of the incidence of hypertension and the knowledge of Indonesian Christian Women (WKRI) members regarding hypertension. This study uses a descriptive quantitative research method with a cross-sectional approach. The results of this study indicate that most of the respondents are in the elderly age group, with a high school education background and homemaker work. The measurement results found that several respondents had hypertension which needed to be reconfirmed by a doctor's diagnosis. In conclusion, it is necessary to carry out periodic controls for hypertension screening of members, and efforts to control consumption and increase knowledge about diet are required. Keywords: Hypertension, Elderly, Knowledge